Persiapan Pelaksanaan Pembelajaran Kurikulum Merdeka Belajar dalam Pembelajaran IPS di SMP Negeri 2 Kademangan - Roro Utari Indra Dewi; Dita Hendriani (Pusat Riset dan Inovasi Nasional, 2024)
The independent learning curriculum is one of the Ministry of Education and Culture's policies with the aim of creating a pleasant and happy learning atmosphere for both teachers and students. In independent learning, teachers and students have the freedom to determine the right learning system to determine the talents and interests of students. The aims of this research are (1) To explain the preparation for the implementation of independent learning curriculum learning in social studies learning at SMP Negeri 2 Kademangan, (2) To explain what factors are obstacles in preparation for implementing independent learning curriculum learning in social studies learning at SMP Negeri 2 Kademangan. This research is qualitative descriptive research. The data collection techniques used in this research are observation, interviews and documentation. Respondents in this research were school principals, head of curriculum, and social science subject teachers. The results of this research show that preparations for implementing the independent learning curriculum in social studies learning at SMP Negeri 2 Kademangan start from the readiness of the teachers first and the social studies teachers take part in training regarding the independent learning curriculum and prepare learning tools according to the provisions of the independent curriculum. Then the factors that are obstacles are (1) Insufficient digital capabilities of teachers, where there are still many teachers who are limited in mastering technology, (2) They are comfortable with the previous curriculum and have no experience in independent learning, (3) lack of facilities and infrastructure to support the learning process, (4) Financial constraints.